Economic Impact of Lyme Disease - Zhang, Xinzhi (Centers for Disease Control and Prevention, 2006)
To assess the economic impact of Lyme disease (LD), the most common vectorborne inflammatory disease in the United States, cost data were collected in 5 counties of the Maryland Eastern Shore from 1997 to 2000. Patients were divided into 5 diagnosis groups, clinically defined early-stage LD, clinically defined late-stage LD, suspected LD, tick bite, and other related complaints. From 1997 to 2000, the mean per patient direct medical cost of early-stage LD decreased from $1,609 to $464 (p<0.05), and the mean per patient direct medical cost of late-stage LD decreased from $4,240 to $1,380 (p<0.05). The expected median of all costs (direct medical cost, indirect medical cost, nonmedical cost, and productivity loss), aggregated across all diagnosis groups of patients, was ≈$281 per patient. These findings will help assess the economics of current and future prevention and control efforts.